Inhibition of the E3 ligase UBR5 stabilizes TERT and protects vascular organoids from oxidative stress - Haijing Zhao; Nian Cao; Qi Liu; Yingyue Zhang; Rui Jin; Huiying Lai; Li Zheng; Honghong Zhang; Yue Zhu; Yuhan Ma; Zengao Yang; Zhengfeng Wu; et al. (Journal of Translational Medicine)
Abstract Background Excessive oxidative stress is known to cause endothelial dysfunction and drive cardiovascular diseases (CVD). While telomerase reverse transcriptase (TERT) shows protective effects against oxidative stress in rodents and is associated to human flow-mediated dilation in CVD, its regulatory mechanisms in human vascular systems under pathological oxidative stress require further investigation. Methods Human induced pluripotent stem cells (hiPSCs) were used to create vascular organoids (VOs). These VOs and human umbilical vein endothelial cells (HUVECs) were subjected to oxidative stress through both hydrogen peroxide (H2O2) and oxidized low-density lipoprotein (oxLDL) models. The effects of TERT overexpression by inhibition of the ubiquitin protein ligase E3 component N-recognin 5 (UBR5) on reactive oxygen species (ROS)-induced vascular injury and cellular senescence were assessed using neovascular sprouting assays, senescence-associated β-galactosidase (SA-β-Gal) staining, and senescence-associated secretory phenotype (SASP) assays. Results ROS significantly impaired VO development and endothelial progenitor cell (EPC) angiogenesis, evidenced by reduced neovascular sprouting and increased senescence markers, including elevated SA-β-Gal activity and SASP-related cytokine levels. Overexpression of TERT counteracted these effects, restoring VO development and EPC function. Immunoprecipitation-mass spectrometry identified UBR5 as a critical TERT regulator, facilitating its degradation. Inhibition of UBR5 stabilized TERT, improving VO angiogenic capacity, and reducing SA-β-Gal activity and SASP cytokine levels. Conclusions Inhibiting UBR5 stabilizes TERT, which preserves EPC angiogenic capacity, reduces VO impairment, and delays endothelial cell senescence under oxidative stress. These findings highlight the potential of targeting UBR5 to enhance vascular health in oxidative stress-related conditions. Graphical Abstract